Secrets of a Successful Pathogen: Legionella Resistance to Progression Along the Autophagic Pathway - Joshi, Amrita D.; Swanson, Michele S. (Frontiers in Microbiology, 2011)
To proliferate within phagocytes, Legionella pneumophila relies on Type IV secretion to modulate host cellular pathways. Autophagy is an evolutionarily conserved degradative pathway that captures and transfers a variety of microbes to lysosomes. Biogenesis of L. pneumophila-containing vacuole and autophagosomes share several features, including ER-derived membranes, contributions by the host GTPases Rab1, Arf1 and Sar1, and a final destiny in lysosomes. We discuss morphological, molecular genetic and immunological data that support the model that, although A/J mouse macrophages efficiently engulf L. pneumophila within autophagosomal membranes, the Type IV effector proteins DrrA/SidM, LidA and RalF prolong association with the ER. By inhibiting immediately delivery to lysosomes, the bacteria persist in immature autophagosomal vacuoles for a period sufficient to differentiate into an acid-resistant, replicative form. Subsequent secretion of the Type IV effector LepB releases the block to autophagosome maturation, and the adapted progeny continue to replicate within autophagolysosomes. Accordingly, L. pneumophila can be exploited as a genetic tool to analyze the recruitment and function of the macrophage autophagy pathway.